Dva pohledy na vývoj nádorů - Šmardová, J; Koptíková, J (Klinicka onkologie, 2016)
BACKGROUND: The somatic mutation theory explaining the process of carcinogenesis is generally accepted. The theory postulates that carcinogenesis begins in a first renegade cell that undergoes gradual transformation from a healthy to a fully malignant state through the accumulation of genetic and epigenetic "hits". This theory focuses specifically on mutations and genetic aberrations, and their impact on cells. It considers tumors as populations of sick cells that lose control of their own proliferation. The theory was put forward by Robert Weinberg and Douglas Hanahan, and is the predominant view in current cancer biology. By contrast, the tissue organization field theory proposed by Carlos Sonnenschein and Ana Soto considers loss of physiological structure and function by a tissue as key events in tumor development. According to this theory, tumors arise at a tissue rather than at a cellular level. It is based on a presumption that proliferation status, rather than quiescence, is the default position of cells in multicellular organisms. AIM: The article aims to provide answers to following questions: Are the views of proponents of the somatic mutation theory (the reductionists) and proponents of the tissue organization field theory (the organicists) incompatible and incommensurable, even when the mainstream of tumor biology has shifted its attention from tumor cells toward the tumor microenvironment? Where to find a third interconnecting systemic approach? Is it useful to be aware of the controversy between reductionists and organicists? What this awareness contributes to? How do these alternative views influence practical oncology and tumor biology in general? CONCLUSION: Whether the true position is held by reductionists or organicists is unimportant. What is important is to be aware of the existence of these two concepts because this knowledge makes the way we think about tumor origin and development, and how we set up and interpret our experiments, more precise. KEY WORDS: carcinogenesis - mutation - cell - tissues - cell proliferation - cell quiescenceThis study was supported by grant of Internal Grant Agency of the Czech ministry of Health No. NT/13784-4/2012.The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 29. 7. 2015Accepted: 27. 4. 2016.
Keywords: mutace; Neoplasms; nádory; karcinogeneze; nádorové mikroprostředí; Humans; proliferace buněk; epigeneze genetická; Tumor Microenvironment; lidé; Mutation; Epigenesis, Genetic; Carcinogenesis; Cell Proliferation